Strengthening policy research on infant and young child feeding: An imperative to support countries in scaling up impact on nutrition - Purnima Menon; Anne Marie Thow (BMC Public Health, 2017)
Abstract Enabling policy environments for nutrition require require evidence to support best practice and engagement with political and policy contexts, as well as leadership, resourcing, advocacy, and technical support. However, research on nutrition policy contexts is limited. The papers in this special supplement on policy contexts for infant and young child feeding (IYCF) in South Asia makes a valuable contribution to understanding the policy landscape and political dynamics in the region and the global literature. Studies included in this special supplement analyzed policy content and stakeholder influence on IYCF in Bangladesh, India, Nepal, Pakistan and Sri Lanka, and assess the role of advocacy in addressing multiple elements of the policy environment. These analyses highlight opportunities to harmonize and manage the demands and interests of multiple actors while strengthening policy to strategically support optimal IYCF as the ultimate goal. They also provide robust examples of research on policy environments and policy change. Further investments in research on policy contexts for nutrition can help to understand and support continued progress towards improved actions for nutrition.